A chromosome-level genome assembly of rugged rose (Rosa rugosa) provides insights into its evolution, ecology, and floral characteristics. (18th June 2021) - Chen, Fei; Su, Liyao; Hu, Shuaiya; Xue, Jia-Yu; Liu, Hui; Liu, Guanhua; Jiang, Yifan; Du, Jianke; Qiao, Yushan; Fan, Yannan; Liu, Huan; Yang, Qi; et al.
Abstract: Rosa rugosa, commonly known as rugged rose, is a perennial ornamental shrub. It produces beautiful flowers with a mild fragrance and colorful seed pods. Unlike many other cultivated roses, R. rugosa adapts to a wide range of habitat types and harsh environmental conditions such as salinity, alkaline, shade, drought, high humidity, and frigid temperatures. Here, we produced and analyzed a high-quality genome sequence for R. rugosa to understand its ecology, floral characteristics and evolution. PacBio HiFi reads were initially used to construct the draft genome of R. rugosa, and then Hi-C sequencing was applied to assemble the contigs into 7 chromosomes. We obtained a 382.6 Mb genome encoding 39, 704 protein-coding genes. The genome of R. rugosa appears to be conserved with no additional whole-genome duplication after the gamma whole-genome triplication (WGT), which occurred ~100 million years ago in the ancestor of core eudicots. Based on a comparative analysis of the high-quality genome assembly of R. rugosa and other high-quality Rosaceae genomes, we found a unique large inverted segment in the Chinese rose R. chinensis and a retroposition in strawberry caused by post-WGT events. We also found that floral development- and stress response signaling-related gene modules were retained after the WGT. Two MADS-box genes involved in floral development and the stress-related transcription factors DREB2A-INTERACTING PROTEIN 2 ( DRIP2 ) and PEPTIDE TRANSPORTER 3 ( PTR3 ) were found to be positively selected in evolution, which may have contributed to the unique ability of this plant to adapt to harsh environments. In summary, the high-quality genome sequence of R. rugosa provides a map for genetic studies and molecular breeding of this plant and enables comparative genomic studies of Rosa in the near future.